Early and midterm results of Cook Formula stent in children with right heart disease: A single-center experience - Haritha Girija; Chinnasamy Sivaprakasam Muthukumaran; Rajaguru Ganesan; Sankarakuttalan Ramkishore; Vijay Arun; Vellusamy Mahitha; Neville Solomon; Swaminathan Vaidyanathan (Annals of Pediatric Cardiology)
Background: Branch pulmonary artery (PA) stenosis must be addressed early to prevent right ventricular scarring and establish lung blood flow. Balloon-mounted stents are more useful in managing right ventricular outflow tract (RVOT) obstruction and PA stenosis. Materials and Methods: We studied the clinical and angiographic data of children with congenital heart disease who underwent stenting for RVOT obstruction and branch PA stenosis using the Formula stent (Cook Medical, Limerick, Ireland) between 2018 and 2024 in a tertiary pediatric cardiac center in southern India. Results: Our patient cohort included 65 patients with a median age of 3 years (range: 3 months to 17 years). The median weight of patients was 11.5 kg (4.8–60.4 kg), with 40% weighing <10 kg. Out of the 87 stents implanted, four stents were implanted in RVOT, while the rest were branch PA stenting. The median stent length was 20 mm (12–60 mm), and the median stent diameter was 10 mm (5–10 mm). All stents were deployed using 5Fr to 8Fr sheaths or guiding catheters. The median procedure time was 62 min (20–170 min), with a median fluoroscopy time of 15 min (4–110 min). A total of 17 (19%) stents in 14 patients required further dilatation at a mean interval of 25 ± 4 months from the time of stenting. Ballooning resulted in an increase in diameter from 7.8 ± 2.2 mm to 10.2 ± 1.7 mm. Right ventricular systolic pressure had reduced from 70.3 ± 8 to 40.1 ± 1 mmHg after balloon dilatation in patients with a biventricular heart. Conclusion: The Formula stent provides a comprehensive stent size option, requiring smaller sheaths, reduced procedural time, minimum complications, and an acceptable rate of reinterventions.